The Quality Management System and its Influence Inside the Process Management of Public Administration - Pereda Lévano, Fabiola Petty (2021)
In order to modernize public management, in the last century, some management models have begun to be applied to achieve their objectives, such as Process Management that conceives the organization as an interrelated system; in addition, it seeks to generate value in products and services that meet customer needs through continuous improvement. On the other hand, there is the Quality Management System, that aims to pursue the objectives, increase the competitiveness of the organization and achieve customer satisfaction; it can be implemented by different models; this article will address the International Standard ISO 9001: Quality Management Systems, which has as one of its principles the approach to processes that promote continuous improvement of the product or service. This article aims to theoretically base the influence of ISO 9001: Quality Management Systems on Process Management and for that effect the bibliographic review method has been used. It will also help public organizations as it focuses on public administration.